From Decision Making to Practice: Economic Growth on Halal Tourism Policies Based on Sharia Regulation in Lombok, Indonesia - SYAMSURRIJAL, M.; NURMANDI, Achmad; JUBBA, Hasse; HIDAYATI, Mega; QODIR, Zuly; ABDULLOH, Irwan (Journal of Environmental Management and Tourism; Vol 14 No 4 (2023): JEMT, Volume XIV, Issue 4(68), Summer 2023, 2023)
This study explores the motivation behind the birth of sharia-based regulations regarding halal tourism in Lombok, focusing on factors beyond religious values and economic development, but also the interests of a sustainable society. This research is case study research using a qualitative descriptive method. The data search process was carried out by means of interviews, observation, and documentation. The data obtained went through several stages of analysis including data reduction, data coding, data display, data triangulation, and drawing conclusions. The findings show that the decision-making process for halal tourism regulation is driven by the desire to accommodate religious values, improve the local economy, and promote sustainable social, cultural , and ecological attractions. The establishment of this regulation is also seen as a political strategy to present Lombok as an international halal tourist destination. This study recommends policymakers consider various factors, including religious values, economic developments, and broader socio-cultural and political strategies, to make policies that benefit society at large